PENGARUH PENERAPAN MODEL PEMBELAJARAN ROUND CLUB TERHADAP HASIL BELAJAR SISWA KELAS VIII SMP PADA MATA PELAJARAN PPKn - Fatolosa Hulu (Jurnal Education and Development, 2020)
The purpose of this study was to determine the effect of the Round Club learning model on cognitive learning outcomes of Grade VIII students of SMP Negeri 1 Toma on PPKn subjects. One solution to influence student learning outcomes, especially in the material of the human digestive system is through the Round Club model where each group is taught to be responsible, give ideas to each other about the material being talked about, and interactions that are built are interactions that provide mutual information and knowledge. This research method is a quasi-experimental method that is quantitative in that the experimental class is used the Round Club model while the control class uses the conventional method. The results of the study were in the experimental class by conducting a pretest an average of 63.57 learning outcomes and an average of 83.21 learning outcomes. While in the control class the pretest obtained an average of 57.93 learning outcomes and posttest obtained an average learning result of 74.66 on the material of the human digestive system of eighth grade students of SMP Negeri 1 Toma. The conclusion of the study is based on the calculation of the hypothesis test known tcount of 2.779 then consulted on the price table t with a significance level of 0.05 where the ttable is 1.673. Because tcount> ttable, Ha is accepted and Ho is rejected at a significant level of 5%, which means "there is an influence of the Round Club learning model on the cognitive learning outcomes of Grade VIII students of SMP Negeri 1 Toma on PPKn subjects.